Violence Beyond the Categories of Life and Death (KULT_online, 2012)
Debrix and Barder's Beyond Biopolitics constitutes an attempt to comprehend forms of violence that escape the current biopolitical paradigm. In proposing the concept of 'agonal sovereignty,' the authors seek to sketch the contours of a particular formation of power that not only supersedes the questions of life and death, but also actively works to undo the distinction between them by inflicting violence upon the already dead body. Although the book's theoretical approach does not seem attuned to local and historical differences, it raises useful questions about both the potential and the limitations of the concept of biopolitics.